Impact of artemether–lumefantrine treatment, circadian rhythm, and serum replacement on the infectiousness of wild Plasmodium falciparum gametocytes to Anopheles gambiae sensu stricto mosquitoes - Mmasi, Dorin Joachim; Kweyamba, Prisca; Matwewe, Fatuma; Maasayi, Masudi Suleiman; Mvungi, Nolvin J.; Kibondo, Ummi Abdul; Habtewold, Tibebu; Stevenson, Jennifer C.; Hofer, Lorenz Martin; Moore, Sarah Jane; Tambwe, Mgeni M. (Frontiers in Malaria, 2025)
BackgroundIn the era of asymptomatic gametocytemia, carriers are scarce but serve as key reservoirs for Plasmodium falciparum gametocytes. Transmission-blocking interventions (TBIs) are gaining attention, considering factors such as artemether–lumefantrine (AL) treatment, mosquito feeding time (day vs. night), and serum replacement, recognized for their potential in influencing direct membrane feeding assay (DMFA) outcomes and reducing assay precision. This study aimed at optimizing DMFA through assessing the following 1) artemether–lumefantrine treatment 2) mosquito feeding time and 3) serum replacement on gametocyte infectiousness to mosquitoes in a low malaria transmission settingMethodsSix gametocytemic carriers were found to be eligible, from whom 4 mL of venous blood was drawn. This blood was given to female Anopheles gambiae sensu stricto (s.s.) mosquitoes via DMFA under controlled conditions. Oocyst prevalence and intensity were determined on fed mosquitoes: 1) 9 days post-AL treatment, 2) for day feeds versus night feeds, and 3) with and without serum replacement.ResultsMosquito infection rates declined post-AL treatment, with significantly fewer mosquitoes infected [odds ratio (OR) = 0.20, 95% confidence interval (CI): 0.13–0.31, p = 0.001] compared to day 0. Feeding during the dark cycle time did not significantly affect mosquito infection rates (OR = 0.77, 95% CI: 0.53–1.12, p = 0.175). Lastly, compared to whole blood, serum replacement increased infection rates (OR = 1.73, 95% CI: 1.33–2.25, p = 0.001).ConclusionTo obtain robust results, we confirm that DMFA should be conducted using blood from gametocytemic carriers without a recent history of AL treatment, using serum replacement to enhance infection success. In this setting, assays could be conducted outside of the mosquitoes’ dark cycle without affecting results.